2022
DOI: 10.3390/ma15031015
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Simulation of a Radiant Floor System: The Impact of Different Screed Mortars and Floor Finishings

Abstract: The radiant floor system market is growing rapidly because Europe is moving toward a low-carbon economy and increased awareness about environmental sustainability and energy efficiency, stimulated by the ambitious EU Energy Efficient Directive and nZEB challenge. The high growth rate of the market share is due to the involvement of homeowners in the specifications of their living commodities, so they are thus willing to invest more at the initial stage to obtain long-term benefits and lower energy exploration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…Na segunda linha de ação, foram utilizados em estudos de simulação numérica os resultados obtidos na fase experimental, para se avaliar o comportamento térmico das argamassas desenvolvidas quando aplicadas num sistema de pavimento radiante hidráulico. Para tal foi usado o software FEMIX num modelo anteriormente calibrado e validado [11]. Os ensaios realizados seguiram as normas vigentes.…”
Section: Procedimentosunclassified
“…Na segunda linha de ação, foram utilizados em estudos de simulação numérica os resultados obtidos na fase experimental, para se avaliar o comportamento térmico das argamassas desenvolvidas quando aplicadas num sistema de pavimento radiante hidráulico. Para tal foi usado o software FEMIX num modelo anteriormente calibrado e validado [11]. Os ensaios realizados seguiram as normas vigentes.…”
Section: Procedimentosunclassified
“…According to the findings of the economic analysis, the system payback period was between 7 and 13 years. Ricardo M. S. F. Almeida et al [5] carried out a three-panel experiment using a radiant floor system of comparable dimensions, shapes, and tubes with various screed mortar formulas. The results demonstrated that the system's efficiency is appropriately impacted by the improved screed mortar.…”
Section: Introductionmentioning
confidence: 99%